Reliability allocation method based on linguistic neutrosophic numbers weight Muirhead mean operator. (1st May 2022) - Li, Guofa; Zhong, Yuan; Chen, Chuanhai; Jin, Tongtong; Liu, Yan
Graphical abstract: Highlights: The fuzzy information is expressed in an intuitive and complete way. A new reliability allocation method is proposed based on LNNWMM operator. The correlation between influencing factors is considered for the first time. A case study is given to illustrate the application in engineering field. More reasonable and flexible allocation of reliability indicators. Abstract: This article presents a reliability allocation method based on Linguistic Neutrosophic Numbers Weight Muirhead mean operator. In order to solve the problem of insufficient consideration of influencing factors in traditional reliability allocation methods, six influencing factors are proposed in the proposed method. Using Linguistic Neutrosophic Numbers, the fuzzy information in the process of reliability allocation can be evaluated completely. The Linguistic Neutrosophic Numbers Weight Muirhead mean operator proposed by this article can process the scoring results by considering the correlation and weight of influencing factors. With the introduction of the safety factor, the exact values of the allocation results can be transformed into interval values. Finally, an example is given to verify the superiority of the proposed method.